Unsteady Flow between Two Orthogonally Moving Porous Disks. (23rd January 2015) - Ghaffar, M.; Ali, K.; Yasmin, A.; Ashraf, M.
Abstract : The unsteady laminar incompressible flow of a fluid between two orthogonally moving porous coaxial disks is considered numerically. A transformation is used to reduce the governing partial differential equations (PDEs) to a set of nonlinear coupled ordinary differential equations. The effects of physical parameters of interest such as the wall expansion ratio and the permeability Reynolds number on the velocity are discussed in detail.